Female excellence in rock climbing likely has an evolutionary origin - Carroll, C. (Current Research in Physiology, 2021)
The human body is exceptional for many reasons, not the least of which is the wide variety of movements it is capable of executing. Because our species is able to execute so many discrete activities, researchers often disagree on which were the movements most essential to the evolution of our species. This paper continues a recently introduced analysis, that the performance gap between female and male athletes narrows in sports which most reflect the movements humans evolved to do. Here, I examine the performance gap in rock climbing. Female climbers are some of the best in the world irrespective of gender, a trend that is not found in any other major sport. I conclude that the exceptional ability of female rock climbers relative to male rock climbers is further evidence of the existence of sex-blind musculoskeletal adaptations, which developed over the course of human evolution - as a result of external (non-sexual) selection forces - to facilitate essential movements. These adaptations abate some of the general physical sexual dimorphism which exists in humans. This paper provides more evidence that the human body was shaped, in part, by pressure to climb well.